Development of a Pichia pastoris strain for secretory production of recombinant alkaline phytase - Vo , Thi Hoang Lan; Chau, Quoc Cuong; Nguyen, Van Hau; Nguyen, Hieu Nghia (Vietnam Journal of Biotechnology, 2025)
Recombinant phytase produced by the Pichia pastoris expression system is widely utilized in the food and animal feed industries. Alkaline phytases are preferred as aquafeed supplements due to their efficiency in degrading antinutritional phytates. In this study, we engineered a recombinant P. pastoris strain to secrete alkaline phytase derived from Bacillus subtilis, with the aim of further application in the aquafeed industry. The recombinant vector, pPICZαA-phy, carrying the phytase-encoding gene (phy), was successfully constructed and integrated into the genome of P. pastoris X33. The resulting recombinant strain, P. pastoris X33::phy, exhibited a methanol-utilization positive phenotype (Mut+) and utilized methanol as a carbon source. Secretion of the recombinant alkaline phytase by P. pastoris X33::phy was confirmed through western blot analysis. Enzymatic activity assay demonstrated that this engineered yeast strain is capable of secreting alkaline phytase, which was able to hydrolyze phytate under mildly alkaline conditions (pH 7.5). These results suggest the potential of this strain for industrial applications, particularly in aquafeed production.